THE STUDY OF OCEAN CURRENT ENERGY POTENTIAL IN LOMBOK STRAIT USING 3-D HYDRODYNAMIC MODEL - CHRISTY RADO TOGARAJA SIMARMATA, AGUNG
This operation of study of ocean current energy in Lombok Strait is divided into two steps. The first step is simulating the ocean current dynamics in Lombok Strait using 3-dimension barothropic hydrodynamic model with ocean tides and sea surface elevation difference between north boundary and south boundary model as generating forces. The model used is Princeton Ocean Model (Mellor, 2004). After ocean current patterns in study areas are obtained, the next step is mapping and analyzing the electrical energy potential that can be extracted from ocean current in Lombok Strait. The analysis is attempted by using CGK Gorlov Helical TurbineÃ‚Â’s performance. It can produce electrical power from ocean current with minimum speed (cut-in speed) of 0.5 m/s, maximum speed (rated speed) of 2.5 m/s, and maximum produced power of 70000 W/m2.Simulation of ocean current is attempted for 29 days simulation period (Februari 2004) with data input consist of bathymetry data, tides data at 8 point on open boundary condition, and sea surface elevation difference between north boundary and south boundary that is taken from global model. The sea surface elevation difference generated by global model is a daily sea surface elevation difference. By using Fraenkel Equation (1999), the electrical power potential that can be generated from ocean current in Lombok Strait is calculated. Two locations from recent research (Nagara, 2006) is picked as the reference for observation location of ocean current pattern. The result of simulation shows that total electrical power potential in one tide cycle reach its maximum value in the area between Nusa Penida Island and Lombok Island (Point A). It reachs 44436.84 W/m2 in spring tide. The other point chosen (Point B) produces electrical power amount 7798.73 W/m2. These electrical powers are produced by using CGK Gorlov Helical Turbine with 0.3m diameter and 0.544m height.